Analisis Perbandingan Kinerja Keuangan Perbankan Sebelum, Selama dan Setelah Masa Pandemi Covid-19 yang Terdaftar Pada Bursa Efek Indonesia - Megasari Wibowo, Efrata; Debora Runtu, Pingkan; Ronald Sumanti, Elvis (Journal of Accounting and Finance Management, 2024)
This research aims to assess the financial performance comparison of banks listed on IDX before, during, and after the COVID-19 pandemic, using financial ratios such as LDR and CAR. A quantitative research method with a comparative approach is utilized. The population includes 48 banking companies listed on the IDX from 2018 to 2024. Statistical methods applied are descriptive analysis and paired sample t-tests. The findings reveal a significant difference in financial performance based on the LDR ratio across the pandemic phases, while no significant difference is observed for the CAR ratio.